Analysis of The Influence of Online Selling, Digital Brand Image and Digital Promotion on Purchase Intention of Instant Noodle Products - Nuraini, Rini; Lamboy Sinaga, Victor; Yusnanto, Tri; Henri Kusnadi, Iwan; Hadayanti, Didit (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to analyze the influence of brand awareness, sales promotions, online advertising, and product attributes on purchase intentions. This research uses a conclusive research design with a descriptive research design. This research data sampling is classified as a single-cross-sectional design. The data collection method is in the form of a questionnaire. This research uses Lisrel to carry out SEM measurements. The research results succeeded in proving that there is a positive influence between brand awareness and sales promotion on purchase intention. Meanwhile, online advertising and product attributes were found not to influence purchase intention. Therefore, it is important for companies that have large advertising costs to improve these factors in various ways. Based on the research results, there are several conclusions that can be drawn. First, product attributes such as taste, packaging, price, and ease of cooking do not have a significant influence on purchase intentions. This shows that the characteristics of the product are not the main factors considered by consumers before making a purchase. Second, online advertising does not have a positive influence on purchase intentions. This may be caused by a lack of attractive and trustworthy advertising messages, according to consumer perception. Third, sales promotions, such as discounts or additional portions, have a significant positive influence on purchase intentions. This shows that consumers tend to be more interested in buying if there is an attractive promotional offer. Finally, brand awareness of the product has a significant influence on purchase intention. This shows that consumers' ability to recognize a brand has an impact on their tendency to buy that product.